Pengembangan Strategi dan Kelayakan Usaha pada Industri Farmasi lokal dalam Menghadapi Persaingan Usaha di PT Bouti Usabda Farma, Solo - da Costa, Yosefine; Hubeis, Musa; Palupi, Nurheni Sri (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2021)
Pharmaceutical industry in Indonesia has made progress and the development of a high around 12-13% in 2013. With high growth indirectly lead to intense competition among the entrepreneurs engaged in this field, especially in the area of Solo, Central Java. Solo City is not a big city like Jakarta, but the competition between the pharmaceutical industry that large, medium and small so large, both in terms of product to service. PT Bouti Usabda Farma is a company engaged in the pharmaceutical field for 21 years since 1992 and now has experienced new growth after the year 2009 the company experienced a split in the internal management. Now the company has only 4 pharmacies courses, where earlier there were 12 pharmacies owned. The purpose of this study is to analyze the problems experienced PT Bouti Usabda Farma, to identify the factors which become obstacles in the face of competition and finding ways for business development and feasibility PT Bouti Usabda Farma. Assessment methods used in this study using the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Strengths, Weaknesses, Opportunities and Threats (SWOT), Quantitative Strategic Planning Matrix (QSPM), Payback Period (PBP) and Break Event Point (BEP). Internal factors are the main problem lies in the lack of Human Resources (HR) power, while the external factors are the biggest threat is the number of similar companies. Farma PT Bouti Usabda lies in quadrant V position and medium flats. Alternative strategies that can be used is the utilization of marketing, technology and capital for business development plan. Judging from the financial side, the company is able to perform in a payback period of 4 years, so the company is worth to be developed.